Proceedings of the 2012 ACM International Conference on Interactive Tabletops and Surfaces 2012
DOI: 10.1145/2396636.2396646
|View full text |Cite
|
Sign up to set email alerts
|

Tabletop games for photo consumption at theme parks

Abstract: This paper broadly explores novel tabletop interaction design opportunities for photo-souvenir consumption in a theme park context. We present the design and user evaluation of two tabletop applications for the playful triaging of photo collections within groups from a day trip to a UK theme park. Combining triaging with gameplay, the designs explore two distinct styles of user interaction, requiring either speed and dexterity or thoughtful strategy. Herein we discuss the rationale for the design process and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
1
3
1
Order By: Relevance
“…We were able to identify only few tabletop-related studies that seek to specify the relation between playfulness and other concepts pertaining to user experience, which is in agreement with the remark made by Anstead et al (2012) that studies of tabletop gaming rarely consider how aspects of gameplay and playfulness may be used as interaction mechanisms within other tasks.…”
Section: Playfulnesssupporting
confidence: 80%
See 1 more Smart Citation
“…We were able to identify only few tabletop-related studies that seek to specify the relation between playfulness and other concepts pertaining to user experience, which is in agreement with the remark made by Anstead et al (2012) that studies of tabletop gaming rarely consider how aspects of gameplay and playfulness may be used as interaction mechanisms within other tasks.…”
Section: Playfulnesssupporting
confidence: 80%
“…Iglesias et al ( 2009) present a playful environment for learning intelligent systems, based on programming soccer teams in the Robocup competition. Anstead et al (2012) developed tabletop ''sideshow games'' that allow small groups (families) to sort and triage photos taken in already playful circumstances-a day trip to a UK theme park. Marchetti and Petersson Brooks (2012a) present Micro-Culture, a game about urban development that was designed as a mixed reality tangible installation containing playful elements that aimed at keeping children's attention focused on the learning content and the game.…”
Section: Tabletops As Appliance and Applicationmentioning
confidence: 99%
“…On average, we found 4.8 (SD=2.5), 5.5 (SD=3.5), and 6.6 (SD=2.8) WA information exchanges in the private, task-dependent, and public modes, respectively. We did not find a significant main effect of either feedback mode (F (2,18) of WA information exchanges. However, we did find a significant interaction between factors (F(2,18)=4.489, p<.05), suggesting that the public feedback mode is more sensitive to distractors than private mode (F(2,18)=7.573, p<.05), increasing total information exchanges.…”
Section: Workpace Awareness Information Exchangescontrasting
confidence: 79%
“…In the past decade, interactive tabletops have been successfully used in multiple domains, including healthcare, education, entertainment, and cultural exhibitions [2,18,34,36]. These devices show significant advantages in supporting multi-user interaction, namely due to their large shared surface.…”
Section: Introductionmentioning
confidence: 99%
“…In HCI however, less has been written about how embarrassment is dealt with in respect of user-generated content. Anstead, et al, [2] compare the impact of embarrassing photos between family and friendship groups in a theme park, concluding that the inclusion of embarrassing footage in souvenirs can negatively impact an individual's public image. In this study we observed participants being equally cautious toward footage in which they were invested.…”
Section: Public Private and Avoiding Embarrassmentmentioning
confidence: 99%